Online education and its relation to hearing status among higher-secondary students in Bangladesh: A cross-sectional survey - Syeda Tasnim Tabassum Hridi; Mohammad Azmain Iktidar; Kazi Sudipta Kabir; Punam Ghosh; Arrafi Tamjid; Abdullah Al Zaber; Rifat Tasnim Babu; Maliha Mehzabeen; Aysharja Das Gupta; Sreshtha Chowdhury; Simanta Roy (PLoS ONE, 2026)
Background Online education gained its popularity in the education system during the COVID-19 pandemic lockdown. The online platform, including social media, was institutionalized globally for the purpose of tutoring to keep the education process ongoing under feasible circumstances. However, the post-pandemic continuation of online education and prolonged usage of electronic devices imposed a greater risk of health issues related to sensory impairment. Our study aimed to determine the impact of online education on students’ hearing status and its associated factors. Methods A cross-sectional study was conducted among 1030 students of 11th grade and above who were undergoing online education in Dhaka and Chattogram. Data were collected through the online administration of a structured questionnaire containing questions on sociodemographic status, family history of diseases, personal history of diseases, information related to screentime exposure, and SSQ-12 (Speech, Spatial, and Qualities of Hearing −12) scale. Descriptive statistics, Pearson’s chi-square test, two independent sample t-tests, and multiple linear regression analysis were employed to obtain the results. Result The mean SSQ score of the study participants was 7.74 ± 1.37. In bivariate analysis, gender, family income, family history of diseases (e.g., obesity, headache, hearing problem), personal history of diseases (e.g., obesity, insomnia), device type (mobile/tablet, computer), average daily screen time with sound, and break pattern during online learning were significantly (p < 0.05 for all) associated with hearing status. In multivariate analysis, being female (coefficient −0.293, p = 0.001), using mobile/tablet (coefficient −0.836, p = 0.001), and continuous screen use (coefficient −0.348, p = 0.003) were significantly associated with poor hearing status. Conclusion This current study indicates the detrimental effect of online education on the hearing of young students in Bangladesh. Future studies should explore the long-term hearing effects of online education and guide the policy makers towards necessary preventive approaches.